«In primary school, you play. In secondary school, you don’t». Transition to secondary education in public schools in Lima. (Revista Peruana de Investigación Educativa, 2017)
The objective of this qualitative study is to explore and describe the perception of students that recently made the transition to secondary school. Twenty students from two different public schools in Lima were interviewed (one offered only secondary education and the other one primary and secondary). An intentional sampling method was implemented and in order to triangulate information a focus group with students from last grade of primary school and interviews with teachers of first grade of secondary education were also conducted. The qualitative analysis provided several findings such as the difference between the expectations that the students had when entering secondary school and what they felt in reality. Students have high educational aspirations, although in reality they found bullying in their classes and violence between schools. Furthermore, teachers have lower academic and behavioral expectations of their students given they are attending the afternoon shift. On the other hand, the simultaneous occurrence of the transition to secondary school and adolescence brings several changes for the students. Their significant adults such as parents and teachers play an important role in this stage. Nevertheless, this study shows that they suddenly decrease the support and supervision over the adolescents. Because of that, the communication between home and school also decreases. This study suggests recommendations for the classroom, school and family to support the students in this transition to secondary.
Keywords: Transitions; secondary school; adolescence; public schools